Optical Properties of Erbium Zinc Tellurite Glass System - Sidek Hj. Abdul Aziz; R. El-Mallawany; Siti Shawaliza Badaron; Halimah Mohamed Kamari; Khamirul Amin Matori (Advances in Materials Science and Engineering)
Er3+-doped tellurite glasses with molar compositions of xEr2O3-20ZnO-(80-x)TeO2 (x=0, 1, 2, 3, and 4 mole%) (EZT) have been successfully synthesized by the melt-quenching method. Density and molar volume have been measured. UV-VIS absorption spectra in the wavelength range of 400–800 nm at room temperature has been measured. The band gap for every composition has been calculated. Photoluminescence spectroscopy in the wavelength range of 400–650 nm and at room temperature has been evaluated.